2007
DOI: 10.1086/521304
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Protection against H5N1 Influenza Virus Infection Is Afforded by Intranasal Inoculation with Seasonal Trivalent Inactivated Influenza Vaccine

Abstract: Intranasal inoculation with annual influenza vaccine plus the Toll-like receptor-3 agonist, poly(I):poly(C(12)U), may overcome the problem of a limited supply of H5N1 virus vaccine by providing cross-protective mucosal immunity against H5N1 viruses with pandemic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 29 publications
6
81
0
Order By: Relevance
“…This is consistent with our previous studies that have shown protection from a lethal homologous H5N1 challenge could be induced in the absence of a classical HI and VN serological response (16). Furthermore, our findings with seasonal adjuvanted vaccines are consistent with those from other studies where cross-protection was demonstrated in the absence of detectable cross-reactive antibodies (10,24). Nevertheless, we show here that antibodies to the H1N1 NA could inhibit the cleavage of fetuin by H5N1 virus, and the levels of these antibodies provided a strong correlate of protection against severe disease and death following H5N1 challenge.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with our previous studies that have shown protection from a lethal homologous H5N1 challenge could be induced in the absence of a classical HI and VN serological response (16). Furthermore, our findings with seasonal adjuvanted vaccines are consistent with those from other studies where cross-protection was demonstrated in the absence of detectable cross-reactive antibodies (10,24). Nevertheless, we show here that antibodies to the H1N1 NA could inhibit the cleavage of fetuin by H5N1 virus, and the levels of these antibodies provided a strong correlate of protection against severe disease and death following H5N1 challenge.…”
Section: Discussionsupporting
confidence: 93%
“…In our evaluation of the effectiveness of a seasonal trivalent split inactivated influenza vaccine (Fluvax) to protect ferrets against lethal H5N1 influenza challenge, we have confirmed the results of other studies demonstrating partial protection (9)(10)(11)(12)(13)(14)(15). However, in this study we have shown that the addition of an adjuvant (either Iscomatrix adjuvant or AlPO 4 ) to the seasonal influenza vaccine affords complete protection in ferrets against severe disease and death due to the highly pathogenic H5N1 virus A/Vietnam/ 1203/04.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, safer adjuvants for clinical use as nasal vaccine adjuvants are required, and many adjuvants are currently being development to improve influenza vaccine efficacy (15,64). We note the usefulness of synthetic RNA poly (I:C), a ligand for TLR 3, as a nasal vaccine adjuvant instead of CT or LT-related materials (15,65,66). However, pathologic effects of double-stranded RNA with respect to age-related macular degeneration (a common cause of irreversible visual impairment) have been reported (67).…”
Section: -3-2 Characteristics Of Ha-specific S-iga Absmentioning
confidence: 99%
“…92,94 In our laboratory, ferrets given seasonal influenza vaccine demonstrated partial protection against H5N1 infection and complete protection against death and disease when vaccines combined with an adjuvant were used (unpublished data). Protection against H5N1 could also be demonstrated in mice following three intranasal inoculations with seasonal vaccine and a Toll-like receptor 3 agonist 95 and in mice and ferrets by the use of intranasal virus-like particles derived from a 1918 influenza isolate. 96 These latter two studies highlighted the potential role of mucosal responses in cross protection.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%